Identifying receptor-like kinases that enable Caulobacter RHG1 to promote plant growth in Arabidopsis thaliana - Amber Lampens; Michiel Vandecasteele; Marjon Braem; Viktor Devlieghere; Judith Van Dingenen; Kris Gevaert; Sofie Goormachtig (Journal of Plant Interactions)
Plants express an array of receptor-like kinases (RLKs) to control development and communicate with their environment. Many RLKs are uncharacterized and some of them are expected to regulate plant responses to plant growth-promoting rhizobacteria (PGPR). Despite documented effects induced by Caulobacter RHG1, the underlying signaling pathways and the involved RLKs remain uncharted. Through a targeted RLK mutant screening, we aimed to decipher the receptors that steer the Caulobacter RHG1-induced growth promotion in Arabidopsis thaliana. We identified four RLKs that are pivotal in the RHG1-Arabidopsis interaction, including the coreceptors SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KINASE 1 (SERK1) and BRASSINOSTEROID INSENSITIVE 1-ASSOCIATED KINASE 1 (BAK1/SERK3), which act redundantly in the RHG1-Arabidopsis interaction, possibly by interplaying with the unknown RLK AT3G28040 and the immunity-related ELONGATION FACTOR-TU RECEPTOR (EFR). These results shed new light on the molecular dynamics orchestrating plant responses to PGPR, and concurrently contribute a crucial piece to the intricate puzzle of RLK interactions.Key policy highlights Four RLKs; BAK1, SERK1, EFR, and AT3G28040 (RRHG) are involved in the RHG1-Arabidopsis interaction.BAK1 and SERK1, two well-described co-receptors, act redundantly and play a pivotal role in the RHG1-driven growth promotion, possibly by interplaying with the unknown RLK AT3G28040 and the immunity-related RLK EFR.Most known development – and immunity-related RLKs barely influence RHG1-driven plant growth promotion in Arabidopsis.